Kebugaran Jasmani Peserta Didik Ditinjau dari Indeks Massa Tubuh, Persentase Lemak Tubuh, dan Aktivitas Fisik - Farhan Dwiki Mailiano Kumaat; Dwi Cahyo Kartiko; Soni Sulistyarto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to analyze the effect of Body Mass Index (BMI), body fat percentage, and physical activity on students’ physical fitness. A quantitative approach with a cross-sectional design was employed. The sample consisted of 150 male and female students of SMAN 1 Baureno in the second semester of the 2024/2025 academic year. Data were collected through BMI measurements, bioelectrical impedance analysis (BIA) for body fat percentage, the International Physical Activity Questionnaire (IPAQ), and the Indonesian Physical Fitness Test (TKJI). Data analysis included descriptive statistics, prerequisite tests, Pearson correlation, and multiple linear regression at a significance level of 0.05. The results indicated that BMI and body fat percentage were significantly negatively correlated with physical fitness, while physical activity showed a significant positive correlation (p < 0.05). Simultaneously, the three variables significantly influenced physical fitness, explaining 47.2% of its variance (R² = 0.472). Body fat percentage emerged as the most dominant predictor. These findings highlight the importance of body composition management and regular physical activity in improving students’ physical fitness. Keywords: Body Fat Percentage, Body Mass Index, Physical Activity, Physical Fitness, Students